Tissue and Exosomal Serine Protease Inhibitors Are Significantly Overexpressed in Chronic Rhinosinusitis With Nasal Polyps - Müller, Sarina Katrin; Nocera, A. L.; Dillon, S. T.; Libermann, T. A.; Wendler, Olaf; Bleier, B. S. (American Journal of Rhinology & Allergy, 2019)
Background: The fibrinolysis pathway has been previously implicated in the etiopathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP). Objective: The purpose of this study was (1) to explore protein derangements of selected protease inhibitors of the serpin superfamily in CRSwNP and (2) to correlate the protease inhibitor derangements of the fibrinolysis pathway in tissue with exosomal samples to evaluate the potential of an exosomal noninvasive “liquid biopsy” for CRSwNP. Methods: Institutional review board approved study in which matched tissue and mucus exosomal proteins (SerpinB2, SerpinF2, SerpinG1, and SerpinE1) were compared between control and CRSwNP patients using Western Blot analysis (n = 6/group) and immunohistochemistry (IHC). Transcriptome analysis (n = 10/group) on the same proteins was performed using whole transcriptome sequencing. Semiquantitative analysis of the Western Blots was performed using the Whitney–Mann U test. Results: The transcriptomic data set showed multiple differentially expressed genes including SerpinB2 (fold changes [FC] 7.38), SerpinE1 (FC 1.42), SerpinF2 (FC 2.03), and SerpinG1 (FC 0.72). Western Blot and IHC analysis showed an overexpression of the Serpin protease inhibitors in tissue (SerpinB2, P <.01; SerpinE1, P <.01; SerpinF2, P <.01; and SerpinG1, P <.01) indicating a downregulation of the fibrinolysis cascade. The mucus exosomal serpin proteins exhibited similar findings. Conclusion: Our analysis supported that protease inhibitors of the fibrinolysis pathway, especially SerpinB2, SerpinF2, and SerpinG1, are highly deranged in patients with CRSwNP. These findings suggest a downregulation of the fibrinolysis pathway via proteolytic cascade imbalance leading to excessive polyp fibrin deposition. Our data further supported our hypothesis that exosomal proteomic analyses may be used as noninvasive “liquid biopsy” for CRSwNP and a novel method to study chronic sinonasal inflammation.
CRIS-Team Scopus Importer:2019-07-30
Keywords: biomarker; chronic rhinosinusitis; inflammation; microarray; nasal polyps; protease; protease inhibitor; sinusitis; Th2 cells; transcriptome